LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP KESEJAHTERAAN KEUANGAN MAHASISWA - Arifin, Andi Harmoko (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of financial literacy and financial behavior on the financial well-being of university students in Indonesia. The research adopts an explanatory quantitative approach with a sample of 150 undergraduate students selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 26. The results show that financial literacy has a significant positive effect on students’ financial well-being (β = 0.452; p < 0.01), and financial behavior also has a significant positive effect (β = 0.375; p < 0.01). Together, both variables explain 62.3% of the variation in financial well-being (F = 122.317; p < 0.01). These findings indicate that financial literacy alone, without healthy financial behavior, is insufficient to improve financial well-being, and vice versa. Therefore, this study recommends the importance of financial education programs that not only focus on enhancing knowledge but also on fostering more disciplined financial behavior among students.